Conduction system pacing upgrade versus biventricular pacing on pacemaker-induced cardiomyopathy: a retrospective observational study - Pei-pei, Ma; Ying, Chen; Yi-heng, Yang; Guo-cao, Li; Cheng-ming, Ma; Qing, Fa; Lian-jun, Gao; Yun-long, Xia; Ying-xue, Dong (Frontiers in Physiology, 2024)
Objective: The feasibility of the conduction system pacing (CSP) upgrade as an alternative modality to the traditional biventricular pacing (BiVP) upgrade in patients with pacemaker-induced cardiomyopathy (PICM) remains uncertain. This study sought to compare two modalities of CSP (His bundle pacing (HBP) and left bundle branch pacing (LBBP)) with BiVP and no upgrades in patients with pacing-induced cardiomyopathy. Methods: This retrospective analysis comprised consecutive patients who underwent either BiVP or CSP upgrade for PICM at the cardiac department from 2017 to 2021. Patients with a follow-up period exceeding 12 months were considered for the final analysis. Results: The final group of patients who underwent upgrades included 48 individuals: 11 with BiVP upgrades, 24 with HBP upgrades, and 13 with LBBP upgrades. Compared to the baseline data, there were significant improvements in cardiac performance at the last follow-up. After the upgrade, the QRS duration (127.81 ± 31.89 vs 177.08 ± 34.35 ms, p < 0.001), NYHA class (2.28 ± 0.70 vs 3.04 ± 0.54, p < 0.05), left ventricular end-diastolic diameter (LVEDD) (54.08 ± 4.80 vs 57.50 ± 4.85 mm, p < 0.05), and left ventricular ejection fraction (LVEF) (44.46% ± 6.39% vs 33.15% ± 5.25%, p < 0.001) were improved. There was a noticeable improvement in LVEF in the CSP group (32.15% ± 3.22% vs 44.95% ± 3.99% (p < 0.001)) and the BiVP group (33.90% ± 3.09% vs 40.83% ± 2.99% (p < 0.001)). The changes in QRS duration were more evident in CSP than in BiVP (56.65 ± 11.71 vs 34.67 ± 13.32, p < 0.001). Similarly, the changes in LVEF (12.8 ± 3.66 vs 6.93 ± 3.04, p < 0.001) and LVEDD (5.80 ± 1.71 vs 3.16 ± 1.35, p < 0.001) were greater in CSP than in BiVP. The changes in LVEDD (p = 0.549) and LVEF (p = 0.570) were similar in the LBBP and HBP groups. The threshold in LBBP was also lower than that in HBP (1.01 ± 0.43 vs 1.33 ± 0.32 V, p = 0.019). Conclusion: The improvement of clinical outcomes in CSP was more significant than in BiVP. CSP may be an alternative therapy to CRT for patients with PICM. LBBP would be a better choice than HBP due to its lower thresholds.